Christian Mission to the Jews Revisited: Exploring the Logic of the Vatican Document “The Gifts and Calling of God are Irrevocable” - Rutishauser, Christian M. (Studies in Christian-Jewish Relations, 2019)
This article examines how the Vatican document "The Gifts and Calling of God are Irrevocable" (2015) deals with the universal claim of Christian faith and the mission of Jesus to make the people of all nations his disciples in relation to Judaism, while the document clearly recognizes that the Jewish people are in an irrevocable covenant with God. The article shows how Church representatives have considered the question since the 1970s and found the formula in dialogue with Jewish representatives with whom the Roman Catholic Church has no institutionalized Jewish mission. The “no” to active mission among Jews and the “yes” to the Jewish-Christian dialogue of the document does not mean, however, that Christians should not testify their faith before all people. Finally, the article considers three topics: historically there have always been Jews and Gentiles who have seen the Messiah in Jesus; the Church sees itself in principle as a church of Gentiles and Jews; and the commitment to religious freedom guarantees Jews and Christians to change sides.